Weight-Length and Condition Factor of Snakehead Fish Channa striata (Bloch, 1793) from Tondano Lake North Sulawesi - Musa Amanpokptis; John L. Tombokan; Nego Elvis Bataragoa; Fransine B. Manginsela (Sam Ratulangi University, 2021)
Sampling was done in two places, Tolour village and Kaweng village. Samples were taken from fishermen in July and August 2018. Total samples collected were 35 individuals, 20 indivduals from Tolour and 15 from Kaweng. Furthermore, the fish were brought the Faculty of Fisheries and Marine Science, and data recording was in the Freshwater Bioecology Laboratory. They consisted of 16 males and 19 females. Male length ranged from 25.8 to 43.2 cm, and female from 22.0 to 39.6 cm. The weight of males ranged from 157-755 g and female between 38-422g.Weight-length relationship in this study was W = 0.0017L3.4517 for sex combination, W = 0.0116L2.9161 for males and W = 0.0009L3,6426 for females. The growth pattern for combied sex was isometric (b = 3.457). The growth pattern was isometric (b = 2.9161) for male and allometric positive (b = 3.6426) for females. The relative condition factor (Kn) of all individuals was 1.06 ± 0.44, 1.01 ± 0.13 for males and 1.01 ± 0.58 for femaleKey Words: Tondano Lake, Snakehead Fish, Weight-length, condition factor ABSTRAKPengambilan sampel dilakukan di dua tempat yaitu, Kelurahan Tolour Kecamatan Tondano Timur dan Desa Kaweng Kecamatan Kakas. Sampel diambil dari hasil tangkapan nelayan pada Bulan Juli dan Agustus 2018. Sampel yang terkumpul sebanyak 35 ekor, 20 sampel dari Tolour dan 15 dari Kaweng. Selanjutnya ikan dibawah ke Laboraturium Bioekologi Air Tawar FPIK untuk pengambilan data. Sampel yang digunakan sebanyak 35 individu yang terdiri atas jenis kelamin jantan 16 individu dan betina 19 individu. Ukuran panjang ikan jantan berkisar antara 25,8-43,2 cm, dan ikan betina berkisar antara 22,0-39,6 cm. Ukuran berat ikan jantan berkisar antara 157-755 g dan ikan betina beratnya berkisar antara 38-422g. Hubungan panjang berat ikan gabus dalam penelitian ini adalah W= 0,0017L3,4517 untuk gabungan jantan betina, W = 0,0116L2,9161 untuk jenis kelamin jantan dan W = 0,0009L3,6426 untuk jenis kelamin betina. Pola pertumbuhan untuk gabungan jantan dan betina adalah isometric (b=3,457). Pola pertumbuhan ikan gabus adalah pola pertumbuhan isometrik (b=2,9161) untuk jantan dan allometrik positif (b=3,6426) untuk jenis kelamin betina. Faktor kondisi relative (Kn) seluruh individu adalah 1,06 ± 0,44. Faktor Kondisi jantan adalah 1,01 ± 0,13. Jenis kelamin betina faktor kondisi adalah 1,01 ± 0,58.Kata kunci: Tondano, ikan gabus, berat-panjag, factor kondisi